Crosstalk between AML and stromal cells triggers acetate secretion through the metabolic rewiring of stromal cells - Vilaplana-Lopera, Nuria; Almaghrabi, Ruba; Papatzikas, Grigorios; Cuminetti, Vincent; Gonzalez, Elena; Jeeves, Mark; Cunningham, Alan; Erdem, Aysegul; Schnuetgen, Frank; Raghavan, Manoj; Potluri, Sandeep; Cazier, Jean-Baptiste; et al. (bioRxiv, 2021)
Acute myeloid leukaemia (AML) cells interact and modulate components of their surrounding microenvironment into their own benefit. Stromal cells have been shown to support AML survival and progression through various mechanisms. Nonetheless, it is unclear whether AML cells could establish beneficial metabolic interactions with stromal cells. Here, we identify a novel metabolic crosstalk between AML and stromal cells where AML cells prompt stromal cells to secrete acetate for their own consumption to feed the tricarboxylic acid cycle (TCA). By performing transcriptome analysis, tracer-based metabolic NMR analysis and ROS measurements, we observe that stromal cells present a higher rate of glycolysis. We also find that acetate in stromal cells is derived from pyruvate via chemical conversion under the influence of reactive oxygen species (ROS) following ROS transfer from AML to stromal cells via gap junctions. Overall, we present a unique metabolic communication between AML and stromal cells that could potentially be exploited for adjuvant therapy. Competing Interest Statement The authors have declared no competing interest. Footnotes * * In vivo (MLL-AF9 mouse model) data has been included in Figure 1G. * Acetate secretion in Thiamine free media has been included in supplementary Figure 5A. *Acetate secretion after modulating ROS levels for Kasumi and HL60 cell lines has been included in supplementary Figure 5B.